An Australian guideline on the diagnosis of overseas-acquired Lyme disease/borreliosis - Lum, Gary D; Hood, Jennie R; Wright, Phil (Communicable Diseases Intelligence, 2015)
Disclaimer: The views expressed in this item are those of the individual authors, and do not necessarily represent the views of the Communicable Diseases Intelligence journal or the Australian Centre for Disease Control. While this Policy and Guidelines item was drafted with consideration to the then-available information on the condition(s) addressed within, it may not be complete and may not represent the currently understood best practice for the referenced condition(s). Readers are advised to refer to the most recent guidance on this matter, where such guidance exists and where its authoritativeness can be established. These guidelines do not replace the need for clinical judgment to be exercised for each individual circumstance, nor the necessity for expert advice to be obtained as appropriate. The Australian Department of Health, with assistance from the Lyme disease Diagnostic Pathway Working Group, has recently developed An Australian guideline on the diagnosis of overseas acquired Lyme Disease/Borreliosis. The document is a diagnostic clinical aid for medical practitioners in Australia who are unfamiliar with Lyme disease acquired overseas.